On the question about prevention of atopic phenotype formation in children born from mothers with bronchial asthma - E. A. Boitsova; T. V. Kosenkova; V. P. Novikova; O. V. Lavrova; I. E. Zazerskaya (Лечащий Врач)
Influence of feeding type on manifestation of atopic diseases in children born from the mothers suffering from bronchial asthma was studied. It was shown that one of the ways of prevention of early manifestation of food allergy clinical symptoms, if breast feeding is impossible, may be use of deep hydrolysis mixtures.